Lexikon Musik und Gender - Kreutziger-Herr, Annette; Unseld, Melanie (Bärenreiter [u.a.], 2010)
Are genius and muse complementary concepts? Are there special music venues for men and women? What were the consequences of the exclusion of girls from central aspects of music education since the Middle Ages? Are notions of masculinity in Heavy Metal confirmed or resolved? In what way are gender norms negotiated on the opera stage? What roles are played by the man-or womanhood with the selection, promotion and memory in music? Is there a connection between music and gender in the areas of analysis, aesthetics and philosophy?
Literaturverz. S. 536 - 577
Keywords: Wörterbuch; Geschichte; Geschlechterrolle; Musik